Analisis Makna Syair Tei Lese Luan di Desa Duarato Kecamatan Lamaknen Kabupaten Belu Kajian Linguistik Budaya - Lusia Yunita Loe; Marselus Robot; Margareta P.E. Djakaho (YASIN, 2026)
Although the Tei Lese Luan poem is an oral tradition of the Bunaq community in Duarato Village, Lamaknen Subdistrict, Belu Regency that encompasses various cultural values, its meanings have not been extensively examined scientifically from the perspective of cultural linguistics. This study aims to analyze the meanings contained in the Tei Lese Luan poem based on cultural linguistics. This study employed a qualitative descriptive method, with data collected through interviews, observation, and documentation. The data were analyzed through the stages of transcription, translation, meaning categorization, and interpretation based on cultural linguistics theory. The findings show that the Tei Lese Luan poem contains seven principal meanings: emotional, historical, symbolic, social, moral, educational, and cultural preservation meanings. From the perspective of cultural linguistics, the poem represents the relationship between language and culture through communal or societal aspects, modes of interaction, and cultural values passed down from generation to generation. The poem also contains three types of imagery: intellectual imagery related to thought processes, tactile imagery related to feelings, touch, and physical experiences, and movement or kinesthetic imagery that strengthens its aesthetic and communicative functions. This study concludes that Tei Lese Luan functions not only as an expression of traditional art but also as a medium for transmitting cultural values, shaping community identity, providing moral education, and strengthening social solidarity. The findings of this study contribute to the development of cultural linguistics studies and support efforts to preserve the oral traditions and local wisdom of the communities in Belu Regency.